IN SITU X-RAY DIFFRACTION STUDY OF POST-SPINEL TRANSFORMATION IN A PERIDOTITE MANTLE: IMPLICATION FOR THE 660-KM DISCONTINUITY - Litasov K.; Ohtani E.; Sano A.; Suzuki A.; Funakoshi K. (My University, 2005)
We present the phase relations in anhydrous CaO-MgO-FeO-Al2 O3-SiO2-pyrolite to examine the influence of compositional difference between pyrolite and Mg2 SiO4 on the post-spinel phase transformation. It is shown that in the pyrolite system the transformation occurs at about 0.5 GPa lower pressure relative to Mg2SiO4. We have carried out several in situ X-ray diffraction experiments on ringwoodite to Mg-perovskite + ferropericlase and backward transformations and found that post-spinel transformation boundary can be expressed as P (GPa) = -0.000 T(K) +54 using the gold equation of state by Tsuchiya [T. Tsuchiya, First-principles prediction of the P-V-T equation of state of gold and the 660-km discontinuity in Earth's mantle, J. Geophys. Res. 108 (2003) doi: 10.1029/2003JB002446]. The interval for coexisting ringwoodite and Mg-perovskite was found to be 0.1-0.5 GPa. The discrepancy between our data and the depth of the seismic discontinuity (global average 654 km) is about 20 km at 1850 K. Based on the results of in situ measurements we confirmed that the difference in chemical composition between pyrolite and Mg2SiO4 cannot modify the Clapeyron slope of the post-spinel transformation. Using experimental data and assuming the average mantle temperature 1850 K at 660 km we can account for only a half of variations in the depth of the 660-km discontinuity in subduction zones and at hot spots. An additional explanation for the observed seismological variations at the 660-km discontinuity is required and may reflect influence of other minor components or volatiles. © 2005 Elsevier B.V. All rights reserved.
Keywords: 660-KM DISCONTINUITY; HIGH PRESSURE; MANTLEMG-PEROVSKITE; PHASE TRANSFORMATION; RINGWOODITE